جاسوسی کی شرعی حیثیت ، حدودوقیود اور عصر حاضر میں اطلاقات: The Islamic Legal Status of Espionage, Its Limits and Applications in the Contemporary Era - Arslan Arif; Hafiz Mudasser Riaz; Qudeer Ahmad (International Research Journal of Arabic and Islamic Studies, 2024)
The basic requirements for becoming a superpower in every era have been knowledge, economic system and military stability. If the Muslim Ummah wants to survive as a nation, it has to become the Imam of the world again in knowledge. It has to be that no enemy rushes on it, but is overwhelmed by their power and hides in their homeland. The kind of strategy that is needed for military stability, spying is the most important part of it, awareness of the enemy's conditions and for success. Acquiring information related to concealment of one's situation, intention of the enemy, determination of their outposts, style of war, number and weapons etc. is very important and this is possible only through spying. For the establishment, defense and stability of the state, where a just ruler and patriotic people are needed, then an army is needed for protection from the enemy. In places where spies are needed to steal operational plans, where thousands of people are needed to build a railway bridge but only a few people are enough to blow it up, many times spies steal important secrets, documents or items. Before the war, they make the enemy so unconscious that it is not time to fight the war. There is a lot of material in the Arabic language about the espionage system of the Holy Prophet, but very little work has been done on this topic in Urdu. Among the works, has written an article called "Islam's System of Spying and Its Exploitation in Contemporary Times". so, my approach in this article will be analytical. After this article of mine, it will be possible to assess what did the Holy Prophet (Peace Be Upon Him) say about the espionage system?